From Conventional to Microservices and NVF: A survey of the paradigm shift in IoT Network System Architecture (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2022)
The contents of this paper can be segregated into two major parts. The first part presents asummarized survey of the conventional Wireless Sensor Network (WSN) architectures alongwith several issues and problems of it. while the second part deals with architecturalmodifications that is observed modern Internet of Things (IoT) networks. The description ofmodern IoT network contains the description distributed computing paradigms (such as Edgeand Fog computing) along with summarized survey of latest techniques such asMicroservices and computational off loadings. The discussion and simulation results led us toenlist some open issues in the concluding section